The onset of active disease in systemic lupus erythematosus patients is characterised by excessive regulatory CD4+-T-cell differentiation - Schaier, Matthias; Gottschalk, Claudius; Kälble, Florian; Uhlmann, Lorenz; Eckstein, Volker; Müller-Tidow, Carsten; Meuer, Stefan; Mahnke, Karsten; Lorenz, Hanns-Martin; Zeier, Martin; Steinborn-Kröhl, Andrea (Clinical and experimental rheumatology, 2021)
OBJECTIVES: An imbalance between CD4+-regulatory T-cells (Tregs) and CD4+-responder T-cells (Tresps) correlates with active disease flares in systemic lupus erythematosus (SLE) patients. Both cell subsets consist of highly proliferating Tregs/Tresps expressing inducible T-cell co-stimulatory molecule (ICOS) and less proliferating ICOS--Tregs/Tresps. METHODS: Six-colour-flow-cytometric analysis was used to examine the effect of ICOS+- and ICOS--Treg/Tresp cell differentiation on the composition of the total CD4+-T-helper cell pool with ICOS+- and ICOS--Tregs/Tresps. Functionality of Tregs was examined using suppression assays. RESULTS: In 83 healthy volunteers, the ratio of ICOS+-Tregs/ICOS+-Tresps increased significantly with age, while that of ICOS--Tregs/ICOS--Tresps did not change. In 86 SLE patients (SLEDAI <7), disease activity was associated with an age-independently increased ratio of both ICOS+-Tregs/ICOS+-Tresps and ICOS--Tregs/ICOS--Tresps. In these patients, the functional activity of ICOS+-Tregs, but not of ICOS--Tregs, was preserved. In 13 markedly active disease patients (SLEDAI >7), the percentage of both ICOS+-Tregs and ICOS+-Tresps, was strongly increased within total CD4+-T-helper cells. However, the increased ratio of ICOS+-Tregs/ICOS+-Tresps was not maintained in these patients, due to terminal differentiation and accumulation of naïve cells within total ICOS+-Tregs. Despite increased differentiation of both ICOS--Tregs and ICOS--Tresps, the percentage of ICOS--Tregs increased within CD4+-T-helper cells, while that of ICOS--Tresps decreased, resulting in a significantly increased ratio of ICOS--Tregs/ICOS--Tresps independent of age. CONCLUSIONS: Our data reveal a crucial role of Treg immune senescence for the occurrence of disease flares in SLE patients, with ICOS+-Treg cells being most affected.
Im Titel ist "+" hochgestellt
Gesehen am 15.07.2021